Using blockchain to create and capture value in the energy sector - Costa, Gonçalo de Andrade Santos Lopes da (2023)
The undergoing digital transition of the energy sector refers to the integration of decentralized ledger technologies and data-driven solutions that have the potential to truly revolutionize its ecosystem and business practices. The aim of a decentralized, inter connected and two-way interactive energy grid can be enabled by leveraging blockchain technologies. This research investigates how blockchain technology can create and capture value from data and the new business models applied in Web 3.0 and blockchain-based environments in the energy sector. A qualitative case study research design was conducted for primary data collection and pilot projects by the European Commission were used for secondary data collection. The analysis shows local energy communities as the main blockchain application in this sector, with adjacent applications such as P2P energy trading, smart contract & metering, carbon trading and grid management. The main benefits associated are transparency, integrity, grid automation and renewable energy sources promotion, and obstacles are mainly associated with the contrasting centralized design of the current energy systems. We conclude that value is created and captured through data provenance and transparency, data monetization and tokenization, and data sharing and collaboration in blockchain platforms. New business models include the decentralization and fusion between energy production and consumption, generating a new actor known as the prosumer. Fundamental to a successful implementation of local energy communities that allow energy and asset trading between peers.